Mediasi Pemerintah Daerah Pada Penyelesaian Sengketa Lahan di Kecamatan Muara Lakitan Kabupaten Musi Rawas - ELMI, ELMI (Jurnal Governance dan Administrasi Publik, 2020)
The purpose of this study was to determine the causes of land disputes and coordination of land dispute resolution in Muara Lakit District, Musi Rawas Regency. This research uses a qualitative approach with a case study method. The Subjects research consisted of community leaders, village administrators, heads of sub-districts, companies (PT. Lonsum) and local governments (Head of Governance and Sub-Section for Cooperation and Regional Autonomy). Data collection techniques include; observation, interview, and documentation. The conclusions in this study include; 1) The local government has conducted mediation, by collecting data and inventorying community reports, making invitations to bring together the two disputing parties, providing opportunities for related parties to administer and documentation, and submitting reports to the Regent and forwarding them to the Governor, so as to resolve land disputes in Muara Rengas Village, Muara Lakit Subdistrict to agree peacefully with the company (PT London Sumatra Indonesia with the Village Head on behalf of the Muara Rengas Community) on March 3, 2017, 2) the land dispute resolution team has coordinated with the Village Head, Sub-District Head and Community Figures formulated recommendations on June 25, 2015 in resolving land disputes in Muara Lakit District, where PT London Sumatra built a plasma plantation for the community, in accordance with the availability of land that has not been planted with oil palm which is in the location permit of PT London Sumatra.